A Small “Tent” in the Esophagus - , Zeng-Min Zong, Jia-Yun Xu, Hai-Tao Zhang, Huan Xu, Xiao-Wei Tang, Lei Shi (Turkish Journal of Gastroenterology 1, 2024)
Cite this article as: Zong Z, Xu J, Zhang H, Xu H, Tang X, Shi L. A small “tent” in the esophagus. Turk J Gastroenterol. 2024;35(7): 587-588.